The Portrait of Policy on Religious Harmony After the Post Reformation in Indonesia - Tholabi Kharlie , Ahmad; M. , Ridwan Kubis (International Journal of Psychosocial Rehabilitation, 2020)
The government policies towards religious development in Indonesia have been running for a long time, or since the colonial era to the reformation. This condition is in line with the fact that the Ministry of Religion is the earliest government institution formed in Indonesia, specifically on January 3rd, 1946. The major problem of this religious development policy is built upon the assumptions of two things: first, the limited transformation in government policy towards religious development, and second, generally speaking, there have been only a limited number of diverse influences on the development programs in Indonesia. The research method applied a qualitative approach and collected the data with in-depth interviews, documentation, focused discussion, and literature studies related to the topic. The research findings reveal that the development of interfaith harmony after the Reformation has not been executed effectively. This is caused by various factors, such as juridical foundation, institutions, programs, socialization, government institutions. Some obstacles related to this are the Forum of Religious Harmony (FKUB) or such institutions formed by the community without any synergy, which makes them run individually. Furthermore, a comprehensive program for such a movement has not been formed that aims to encourage solidarity among groups. Therefore, the socialization of harmony is a crucial matter considering a distortion of harmony in the community's perspective. The performing activities can be implemented through formal and informal activities. Spreading information can be done verbally or in writing, including the creation of banners, leaflets, and advertisements. Supplementary to this, FKUB needs to approach educational institutions ranging from early childhood education, kindergarten, elementary school, junior high school, high school, and higher education to become a future successor.